2009
DOI: 10.1007/s11605-009-0828-4
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Institution Experience with Eight CD117-Positive Primary Extragastrointestinal Stromal Tumors: Critical Appraisal and a Comparison with Their Gastrointestinal Counterparts

Abstract: The occurrence of true EGISTs is rare. Most cases demonstrate some form of communication or contact with the gut wall, and EGISTs are significantly larger than extramural or intra/transmural GIST. These observations suggest that most, if not all, cases of EGISTs are likely to represent mural GISTs with extensive extramural growth with eventual loss of contact with the muscle layer of the gut.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 17 publications
1
61
0
Order By: Relevance
“…Agaimi et al (9) reported in their series that the rate of EGIST is lower than expected (1.5%) and that some of these tumors are actually masses protruding out of the gastrointestinal canal and eventually lost its communication to the tract due to trauma or during surgery (8-10). Goh et al (10), in a series of 8 EGIST cases reported that 6 patients had a relation with the GI tract (2 muscular, 4 serosal communication) have reported. In patients with EGIST localized to the liver, the origin is thought to be metastases from unnoticed origin or previous surgical interventions performed for other reasons (9,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Agaimi et al (9) reported in their series that the rate of EGIST is lower than expected (1.5%) and that some of these tumors are actually masses protruding out of the gastrointestinal canal and eventually lost its communication to the tract due to trauma or during surgery (8-10). Goh et al (10), in a series of 8 EGIST cases reported that 6 patients had a relation with the GI tract (2 muscular, 4 serosal communication) have reported. In patients with EGIST localized to the liver, the origin is thought to be metastases from unnoticed origin or previous surgical interventions performed for other reasons (9,11).…”
Section: Discussionmentioning
confidence: 99%
“…GISTs are the most common tumors of mesenchymal tissue origin in the gastrointestinal tract, and although it is reported that they can arise outside the digestive system in 5-10%, its true frequency is considered to be even less (7,9,10). The origin of EGIST cases located in the omentum, mesentery or retroperitoneum is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Goh et al, suggested that most, if not all, cases of EGISTs are likely to represent mural GISTs with extensive extramural growth with eventual loss of contact with the muscle layer of the gut. 10 Approximately 80% are located in the omentum or mesentery and the remainder develop in the retroperitoneum rarely from gallbladder and urinary bladder. 4 Gross appearance of EGISTs varies from firm, fleshy gray-red masses to cystic ones.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of EGISTs is uncertain but as a rule, their histological appearances and immunophenotype are identical to those of classical GISTs. They are therefore thought to represent either GISTs that have separated from the GI tract wall [8], or independent growths of pluripotent precursor mesenchymal cells of the omentum and mesentery, from which ICCs originate [9,10]. KIT and PDGFRA mutations are also present in EGISTs [11].…”
Section: Introductionmentioning
confidence: 99%